Coronary CT angiography: Dose reduction strategies - Sabarudin, Akmal; Sun, Zhonghua (Beijing Baishideng BioMed Scientific Co., Ltd, 2013)
With the introduction of 64- and post-64 slice computed tomography (CT) technology, coronary CT angiography has been increasingly used as a less invasive modality for the diagnosis of coronary artery disease. Despite its high diagnostic value and promising results compared to invasive coronary angiography, coronary CT angiography is associated with high radiation dose, leading to potential risk of radiation-induced cancer. A variety of dose-reduction strategies have been reported recently to reduce radiation dose with effective outcomes having been achieved. This article presents an overview of the various methods currently used for radiation dose reduction.